2013
DOI: 10.1186/1423-0127-20-57
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor (Val66Met) polymorphism and olfactory ability in young adults

Abstract: BackgroundBrain- derived neurotrophic factor (BDNF) is linked to neurodegenerative diseases (e.g. Alzheimer disease and Parkinson disease) which are often characterized by olfactory impairment. A specific single nucleotide polymorphism of the BDNF gene, the Val66Met, modulates intracellular trafficking and activity-dependent secretion of BDNF protein. The aim of this study was to investigate a possible association between brain- derived neurotrophic factor Val66Met polymorphism and olfactory function, a well-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
2
13
2
Order By: Relevance
“…Interestingly, executive as well as olfactory functions are both mediated by BDNF neurotrophins secreted over frontal brain areas, a region particularly vulnerable to concussions. In this study, better olfactory function performance specific to BDNF Met concussed athletes is at odds with previous uninjured animal models and healthy participants that rather linked the BDNF Met variant with diminished olfactory functioning [43,50]. As suggested by Barbey et al [41], the functional effect of the BDNF Met allele may differ under normal and pathological conditions.…”
Section: Main Findingscontrasting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, executive as well as olfactory functions are both mediated by BDNF neurotrophins secreted over frontal brain areas, a region particularly vulnerable to concussions. In this study, better olfactory function performance specific to BDNF Met concussed athletes is at odds with previous uninjured animal models and healthy participants that rather linked the BDNF Met variant with diminished olfactory functioning [43,50]. As suggested by Barbey et al [41], the functional effect of the BDNF Met allele may differ under normal and pathological conditions.…”
Section: Main Findingscontrasting
confidence: 53%
“…A study by Hedner et al [49] revealed no effect of the BDNF Val66Met polymorphism on olfactory function in healthy young adults, whereas healthy older adults carrying the wild-type BDNF Val66Val (BDNF Val ) genotype and not the expected sub-group of BDNF Met carriers exhibited significantly reduced olfactory function. Another study conducted in young healthy adults using the Sniffin' Sticks Inventory Test (SSIT), a standardized battery of olfactory function tests with improved psychophysical properties, showed that carrying the BDNF Met genotype significantly reduced olfactory function [50]. The use of the SSIT allows a more detailed evaluation of olfactory functions, when compared to more traditional scratch-and-sniff tests, by looking at olfactory threshold, discrimination and identification for a better characterization of the deficits observed.…”
Section: Introductionmentioning
confidence: 98%
“…Checking of analysis sorted participants to three genetic categories: val/val (46 people), val/met (40 people), and met/met (14 people). The genotype's distribution of Val66Met polymorphism observed in both val/val and val/ met genotype satisfied the Hardy-Weinberg Equilibrium and were comparable with that previously observed in previous studies [17][18][19] . The experiment leader in this study was blinded for the genotype of the participants.…”
Section: Bdnf Genotypingsupporting
confidence: 77%
“…A more relevant common gene to AD and ASD is the brain-derived neurotrophic factor (BDNF) gene, which plays an important role in neurogenesis, cortical lamination, synaptic plasticity, and neuron survival [82,83]. Several studies, directly or indirectly, suggest an involvement of BDNF in ASD, usually showing that BDNF levels in the blood, serum and brain are increased in children with ASD compared with TD children [84].…”
Section: Genetic Backgroundmentioning
confidence: 99%